Edukasi Masyarakat terhadap Pemanfaatan Limbah Minyak Jelantah Menjadi Lilin Aromaterapi - Yulia Nur Azizah; Titis Cindy Marcella; Uswatun Nafi'ah; Wanda Nisa' Mutiara Salsabila; Widya Rahma Rofiyanti (Yayasan Literasi Sains Indonesia, 2025)
One strategic community empowerment program is training on making aromatherapy candles from used cooking oil. The main goal of this program is to increase public understanding and skills in how to creatively and sustainably manage household waste. This program aims to educate people on how to transform useless waste into products with great economic potential. In Melis Village, Gandusari District, Trenggalek Regency, there are 15 participants consisting of Family Welfare Empowerment (PKK) cadres and active community members. The training was held at the home of one of the local posyandu cadres, strategically chosen and easily accessible to the participants. The learning method used is direct (hands-on training), where participants not only listen to theoretical explanations but also actively observe and practice each step of the aromatherapy candle-making process. During this process, participants learn methods of purifying used cooking oil using activated charcoal to remove dark color and rancid odor, as well as how to mix it with ingredients like paraffin, wax dyes, and essential oils to give the wax a natural scent. Direct experience that facilitates participants' understanding and skills is gained thru a participatory approach and hands-on practice. The training results show that the community can make environmentally friendly, esthetically pleasing, and potentially profitable aromatherapy candles. It is hoped that this training will not be a temporary activity; it will be a starting point for building a handicraft business using recycled materials in Melis Village and raising awareness about the importance of managing household waste sustainably and responsibly.